Mimesis and Pacific transcultural encounters : making likenesses in time, trade, and ritual reconfigurations - Mageo, Jeannette Marie, 1947-; Hermann, Elfriede (ASAO studies in Pacific anthropology ;, 2017)
How do images circulating in Pacific cultures and exchanged between them and their many visitors transform meanings for all involved? This fascinating collection explores how through mimesis, wayfarers and locales alike borrow images from one another to expand their cultural repertoire of meanings or borrow images from their own past to validate their identities.